The hemşehrilik and the village: the stakes of an association of former villagers in Ankara - Benoit Fliche (European Journal of Turkish Studies)
This article analyses the reasons behind the successes and failures of collective actions intiated by an association of former villagers. Members of this association did not adhere to all these collective actions, as these must be acceptable in semiotic terms, and must also conform to the hemşehrilik egalitarian ideal. One of the main obstacles to associative mobilisation is that the village itself is a conflictual and competitive place. This contrast between village and association shows that this is more an association of hemşehri than a village association. This difference invites us to reconsider the relationship which former villagers can (or cannot) have with their village, and to question the signification of the term hemşehri.